THE EFFECT OF DIFFERENT DRYING TIME TO NORI SEAWEED (Gracialaria sp.) QUALITY - Desti Nurfiani; N. Ira Sari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of the research was to determine the effect of different drying time to nori seaweed (Gracilaria sp.) The method used was experimental with different of drying time of nori seaweed processing. The method used was experimental and composed as non factorial Completely Randomized Design (RAL), which consisted of 3 levels,namely:long drying 18, 20 and 22 hours. The parameters used were sensory evaluation, the value of water content, ash content, and fiber content. Based on parameters of different drying time to nori seaweed the best treatment was long drying 22 hours with appearance (6.17), flavor (8,01), taste(7,61) and texture(8,15) with characterictics appearance is green, fragrant aroma, good with specific seaweed taste, and rough and crisp textures.the chemical values obtained water content (12,97%), ash content (0,70%) and fiber content (8,12%).Keywords: nori seaweed, Gracilaria sp., drying